Spatial and temporal changes in rainfall in the southern zone of Tamil Nadu-An analysis - Premavathi , R; Suganthi , N; Sudha, R; Kanaga, S; Kamali , S P; Ponsneka, I; Sasikala, R (Plant Science Today, 2025)
Rainfall plays a crucial role in planning and managing water resources. Climate fluctuations significantly impact water availability and rainfall patterns. This study analyses spatiotemporal changes and trends in extreme rainfall events from 1990 - 2022 in the Ramanathapuram district of Tamil Nadu. It also compares seasonal rainfall variability across four districts-Ramanathapuram, Virudhunagar, Sivaganga and Madurai-within the southern zone. The study employs Markov Chain modelling, the Mann-Kendall trend test and compound growth rate analysis, utilising secondary data from government sources. The findings indicate significant shifts in the pattern of rainfall in Ramanathapuram, exhibiting a downward trend. The transition matrix suggests a 75 % chance of heavy rain in November. The results provide significant insights into climate variability and its impacts on sustainable agriculture, suggesting that farmers plan for a better cropping system in advance to achieve a higher yield.